Historical Perspectives of Shifting Motives for Faith-Based Travel - Munro, Dane (The international journal of religious tourism and pilgrimage, 2017)
Throughout pre-history and history, millions of people of many religions and faiths have undertaken pilgrimages. Although the quintessential form of religiously motivated travel is pilgrimage', the meaning of the practice of pilgrimage has changed over the centuries (Dietz, 2005:27). There are also some consistent Leitmotifs and principles in religious travel. Participants of the New Religious Movements (NRM) travel to Neolithic and other prehistoric sites (such as Malta) for a spiritual experience at such sites, seeking to fulfil needs which the historic churches cannot or no longer can fulfil. (Rountree, 2002:475-496). Many NRMs are based on historical values, past religions or on symbolical or perceived values of the Neolithic past (Hutton, 1990:351-8). Others come to Malta for a traditional pilgrimage or a trip with religious aspects which fit with the traditional aspects of religious Malta, related to the Pauline or Marian cults. The present writer prefers to use the term faith-based tourism' when it comes to Malta, because everyone arriving to Malta has to use part of the tourism infrastructure. Besides, faith-based tourism is an umbrella term, encompassing pilgrimage, religious travel, tourism with a religious theme and secular pilgrimage, because even in the latter form there are spiritual aspects and elements of faith present.